2003
DOI: 10.1046/j.1365-2958.2003.03501.x
|View full text |Cite
|
Sign up to set email alerts
|

TFIIB and subunits of the SAGA complex are involved in transcriptional activation of phospholipid biosynthetic genes by the regulatory protein Ino2 in the yeastSaccharomyces cerevisiae

Abstract: SummaryIn the yeast Saccharomyces cerevisiae , genes involved in phospholipid biosynthesis are activated by ICRE (inositol/choline-responsive element) upstream motifs and the corresponding heterodimeric binding factor, Ino2 + + + + Ino4. Both Ino2 and Ino4 contain basic helix-loop-helix (bHLH) domains required for ICRE binding, whereas transcriptional activation is mediated exclusively by Ino2. In this work, we describe a molecular analysis of functional minimal domains responsible for specific DNA recognition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 69 publications
(104 reference statements)
2
59
0
Order By: Relevance
“…48 Acetylation by the catalytic subunit of SAGA, the Gcn5 protein, promotes transcription initiation of the INO1 and GAL1 genes, both of which are targeted to the nuclear periphery upon activation. 49,50 Therefore, localization to the nuclear periphery may help overcome rate-limiting steps in transcription initiation by providing increased access to SAGA components. Though this is an attractive model for the INO1 and GAL1 genes, it does not explain the role of NPC interaction in the transcription of TSA2, a gene not regulated at the level of chromatin.…”
Section: Discussionmentioning
confidence: 99%
“…48 Acetylation by the catalytic subunit of SAGA, the Gcn5 protein, promotes transcription initiation of the INO1 and GAL1 genes, both of which are targeted to the nuclear periphery upon activation. 49,50 Therefore, localization to the nuclear periphery may help overcome rate-limiting steps in transcription initiation by providing increased access to SAGA components. Though this is an attractive model for the INO1 and GAL1 genes, it does not explain the role of NPC interaction in the transcription of TSA2, a gene not regulated at the level of chromatin.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, recruitment of histone acetyltransferases (HATs) and deacetylases (HDACs), histon methyltransferases (HMTs) and demethylases (HDMs) essentially aVects the access of the transcriptional machinery to promoter regions. We and others have previously shown that the HAT complex SAGA contributes to Ino2-dependent gene activation (Dietz et al 2003;Lo et al 2005). However, SAGA is not recruited directly but instead requires phosphorylation of histone H3 at Ser10 by the histone kinase Snf1 which is bound by Ino2.…”
Section: Introductionmentioning
confidence: 94%
“…While Ino4 is required for ICRE binding and nuclear import of the complex, transcriptional activation is mediated exclusively by Ino2 containing two separate activation domains (Schwank et al 1995;Dietz et al 2003;Kumme et al 2008). Activation of target genes occurs when the supply of phospholipid precursors inositol and choline is limiting, leading to an excess of phosphatidic acid (PA) which prevents nuclear localization of repressor Opi1 (Loewen et al 2004; reviewed by Chen et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One class is preferentially targeted by the Spt-Ada-GCN5-acetyltransferase (SAGA) transcriptional complex and contains many stress-inducible genes (Ϸ10% of the genome), whereas the other class is preferentially targeted by the TFIID transcriptional complex and associated with house-keeping functions (Ϸ90% of the genome). TFIIB cooperates with the yeast SAGA complex (25), and it is possible that similar interactions direct TFIIB function during osmotic stress in vertebrates.…”
Section: Significance Of Osmotic Regulation Of General Transcription mentioning
confidence: 99%